Impact of Socioeconomic Status and Race on Sepsis Epidemiology and Outcomes. (26th November 2020) - Minejima, Emi; Wong-Beringer, Annie
Abstract: Background: Socioeconomic status (SES) is a complex variable that is derived primarily from an individual's education, income, and occupation and has been found to be inversely related to outcomes of health conditions. Sepsis is the sixth most common admitting diagnosis and one of the most costly conditions for in-hospital spending in the United States. The objective of this review is to report on the relationship between SES and sepsis incidence and associated outcomes. Content: Sepsis epidemiology varies when explored by race, education, geographic location, income, and insurance status. Sepsis incidence was significantly increased in individuals of Black race compared with non-Hispanic white race; in persons who have less formal education, who lack insurance, and who have low income; and in certain US regions. People with low SES are likely to have onset of sepsis significantly earlier in life and to have poorly controlled comorbidities compared with those with higher SES. Sepsis mortality and hospital readmission is increased in individuals who lack insurance, who reside in low-income or medically underserved areas, who live far from healthcare, and who lack higher level education; however, a person's race was not consistently found to increase mortality. Summary: Interventions to minimize healthcare disparity for individuals with low SES should target sepsis prevention with increasing measures for preventive care for chronic conditions. Significant barriers described for access to care by people with low SES include cost, transportation, poor health literacy, and lack of a social network. Future studies should include polysocial risk scores that are consistently defined to allow for meaningful comparison across studies.